Analysis the Effect of Size Variation and Spraying Pressure of Steel Grit on Corrosion Rate of Astm A36 Steel Materials - Ari Wibawa Budi Santosa; Iqbal Fahrudin; Ocid Mursid; Imam Pujo Mulyatno; Joko Subekti (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
ASTM A36 steel is a steel commonly used in shipbuilding construction. The property of steel that is highly avoided is susceptible to corrosion or corrosive which can reduce the strength of the structure. Over time, technology has developed, and methods have been found to inhibit the rapid rate of corrosion, coating process is one of them. The success rate of coating process is also strongly influenced by the surface preparation process. The surface preparation process in this study was by differentiating the size variations of the SG18, SG25, and SG40 steel grit abrasive materials and the spraying pressure of the 5 bar, 6 bar, and 7 bar abrasive materials and the provision of scratch defects on the specimens that had been coated with epoxy primer paint. The purpose of the research conducted was to analyze variations in size of the abrasive material, the spraying pressure of the abrasive material, and which combination of variations is the best for specimens considered to have been scratched. In each variation, the value of the corrosion rate will be increased when the size of the material increased and the value of the corrosion rate increases when the spraying pressure decreases. The results obtained from this study indicate that the lowest corrosion rate value is 0.0027 mmpy with the outstanding category of the variation used, which is grit SG40 steel abrasive material and at a pressure of 7 bar.